2020
DOI: 10.5194/wes-2020-55
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Augmented Kalman filter with a reduced mechanical model to estimate tower loads on an onshore wind turbine: a digital twin concept

Abstract: Abstract. The paper presents an application of the Kalman filtering technique to estimate loads on a wind turbine. The approach combines a mechanical model and a set of measurements to estimate signals that are not available in the measurements, such as: wind speed, thrust, tower position, and tower loads. The model is several fold faster than real-time and is intended to be run online, for instance, to evaluate real-time fatigue life consumption of a field turbine using a digital twin. The mechanical model is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Coupling sensor data with models of the turbine allows the creation of "digital twins" of wind turbines (Rinker et al, 2018). These software representations of hardware are now available as commercial services and are frequently used for tracking turbine fatigue loading and remaining lifetimes (Branlard et al, 2020). Research is ongoing on ways to use this data to make intelligent control decisions (Pettas et al, 2018).…”
Section: Opportunities For the Use Of Datamentioning
confidence: 99%
“…Coupling sensor data with models of the turbine allows the creation of "digital twins" of wind turbines (Rinker et al, 2018). These software representations of hardware are now available as commercial services and are frequently used for tracking turbine fatigue loading and remaining lifetimes (Branlard et al, 2020). Research is ongoing on ways to use this data to make intelligent control decisions (Pettas et al, 2018).…”
Section: Opportunities For the Use Of Datamentioning
confidence: 99%
“…In Fig. 6, we classified and referenced the latest case studies of DT usage reported in the literature for different innovative industries that come under the vision of Industry 4.0, i.e., manufacturing [60]- [63], automobile [64]- [67], aerospace [68]- [71], windfarm [72]- [75], and healthcare [76]- [79]. Moreover, Fig.…”
Section: B the Role Of Dt Across Industriesmentioning
confidence: 99%